1970
DOI: 10.1063/1.1653208
|View full text |Cite
|
Sign up to set email alerts
|

The Lattice Location of Boron Ions Implanted Into Silicon

Abstract: Channeling-effect measurements have been used to investigate the lattice location of boron atoms implanted into silicon at an energy of 56 keV and with doses in the interval 1014–1015 ions/cm2. Measurements have been made as a function of implantation temperature and subsequent anneal treatment. The effect of post-bombardment with different doses of 680-keV protons has also been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
3
3

Year Published

1974
1974
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(13 citation statements)
references
References 7 publications
0
7
3
3
Order By: Relevance
“…This annealing behaviour is in contrast to that observed for Si which had been implanted with B at room temperature [30,31] (but not subsequently annealed), where the fraction of displaced B atoms increased during annealing from 450-750 K. It can be concluded that the implantation damage produced a different and probably more complicated defect configuration containing B. This is expected because the defect distribution produced in cascades from r 50 keV B ion irradiation is more complex than that from 0.7 MeV H+ irradiation.…”
Section: Angular Scanscontrasting
confidence: 81%
See 1 more Smart Citation
“…This annealing behaviour is in contrast to that observed for Si which had been implanted with B at room temperature [30,31] (but not subsequently annealed), where the fraction of displaced B atoms increased during annealing from 450-750 K. It can be concluded that the implantation damage produced a different and probably more complicated defect configuration containing B. This is expected because the defect distribution produced in cascades from r 50 keV B ion irradiation is more complex than that from 0.7 MeV H+ irradiation.…”
Section: Angular Scanscontrasting
confidence: 81%
“…One of the samples had been irradiated with 0.7 MeV H to a fluence of 7 x 1016 cm-2 at 35 K, and the second sample had been irradiated to a fluence of 4 x 10 16 cm-2 at 300 K. The major displacement of B atoms occurred during an annealing stage centered at 240 K (as observed previously for a thermally diffused crystal [20]), while the recovery of this B atom displacement occurred over a broad temperature range from 425-825 K. This latter recovery behaviour was in marked contrast to that reported [30,31] for The apparent displaced fraction of B atoms fd<lmn> for <100> and <110> channels is shown as a function of annealing temperature (600 s pulse anneals) for two samples.…”
Section: Annealingcontrasting
confidence: 57%
“…The value of boron atoms sited in the substitution position after implantation depends on the dose of ion implantation and may exceed 60%. 37 The annealing at 500-950°C is usually accompanied by the process of reverse annealing of the doping impurities. During this process impurities escape from the substitution position in the semiconductor lattice into the interstitial position.…”
Section: Discussionmentioning
confidence: 99%
“…Several properties of the 1.018 eV peak (11) have been investigated, and certain conclusions can be drawn about the defect's luminescence. The half-width of the I1 peak follows a nonlinear dependence on sample temperature, suggesting bound carrier to bound carrier transitions.'…”
Section: Figurementioning
confidence: 99%